An integrated CVaR and real options approach to investments in the energy sector - Ines Fortin; Sabine Fuss; Jaroslava Hlouskova; Nikolay Khabarov; Michael Obersteiner; Jana Szolgayova (Institute for Advanced Studies (IHS), 2007)
The objective of this paper is to combine a real options framework with portfolio optimization techniques and to apply this new framework to investments in the electricity sector. In particular, a real options model is used to assess the adoption decision of particular technologies under uncertainty. These technologies are coal-fired power plants, biomassfired power plants and onshore wind mills, and they are representative of technologies based on fossil fuels, biomass and renewables, respectively. The return distributions resulting from this analysis are then used as an input to a portfolio optimization, where the measure of risk is the Conditional Value-at-Risk (CVaR).
Keywords: C61; D81; D92; G11; Q4; Q56; Q58; 330; portfolio optimization; CVaR; climate change policy; uncertainty; real options; electricity; investments; Portfolio-Management; Risikomaß; Investitionsrisiko; Realoption; Elektrizitätswirtschaft; Umweltpolitik; Schätzung; OECD-Staaten